Neonatal hypercalcemia secondary to subcutaneous fat necrosis presenting as severe dehydration - Anu Garg; Ravish Singhal; Shyam Sundar Chaudhary (Wolters Kluwer Medknow Publications, 2018)
Subcutaneous fat necrosis (SCFN) is a rare fat tissue inflammation of the newborn that generally occurs in term or postterm newborns exposed to perinatal stressing factors such as cord prolapse, perinatal asphyxia, therapeutic hypothermia, meconium aspiration, and sepsis. Although most cases of SCFN resolve spontaneously, SCFN may be associated with symptomatic hypercalcemia presenting as lethargy, hypotonia, irritability, vomiting, polyuria, polydipsia, constipation, and dehydration. We describe a case of newborn affected with the disease, its presentation, clinical course, and treatment.